A street canyon model for low wind-speed conditions. (1st January 2001) - Coppalle, A.
The aim of the present work is to develop a simple model in order to calculate the vertical pollutant distribution inside a street canyon at low wind speed. It is aimed at providing a relationship between traffic emission and the pollutant in excess. It is assumed that street ventilation is controlled by the vertical turbulent diffusion. The diffusion coefficient Kz must be known. In the present study, the correlation between calculated and experimental values will be shown, which makes it possible to estimate this parameter.